2011
DOI: 10.1007/s11524-011-9602-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Shelter Use and Housing Placement on Mortality Hazard for Unaccompanied Adults and Adults in Family Households Entering New York City Shelters: 1990–2002

Abstract: This study examines mortality among New York City (NYC) homeless shelter users, assessing the relationships between mortality hazard and time in shelter, patterns of homelessness, and subsequent housing exits for both adults in families and single adults. Administrative records from the NYC shelter system were matched with death records from the Social Security Administration for 160,525 persons. Crude mortality rates and life tables were calculated, and survival analyses were undertaken using these data. Life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 43 publications
4
38
0
Order By: Relevance
“…Similar to prior studies, 6, 12, 18 we found significantly higher mortality rates among white homeless adults in comparison to other racial groups, which differs from the pattern in the general population. This may reflect underlying racial differences in the pathways to homelessness.…”
Section: Commentsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to prior studies, 6, 12, 18 we found significantly higher mortality rates among white homeless adults in comparison to other racial groups, which differs from the pattern in the general population. This may reflect underlying racial differences in the pathways to homelessness.…”
Section: Commentsupporting
confidence: 87%
“…Our study included both currently and formerly homeless adults, which likely exerts a conservative bias on our findings since individuals who have exited homelessness may have lower mortality rates. 18 Finally, the accuracy of death certificates in identifying cause of death has been debated. 47 Death certificates have poor sensitivity but high specificity for identifying drug poisoning deaths, 48 implying a low likelihood for “false positive” drug overdose deaths in our study.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the aging of the single adult homeless population raises serious questions about the near future of those who are currently homeless and the age cohort from which they come. With this population heavily concentrated in the 46 to 57 age range and evidence showing the average life expectancy of homeless single adults to be 64 years, (Metraux, Eng, Bainbridge, & Culhane, 2011) aging related health needs are likely to become a substantial problem among the single adult homeless population in the very near term. Indeed, a recent study found that, when compared to members of the general population aged 50 and above, homeless adults in the same age bracket had significantly higher rates of a number of geriatric symptoms including difficulty performing activities of daily living (ADLs), mobility and cognitive impairment, frailty, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Among older homeless adults, there are high rates of chronic diseases, cognitive and functional impairments (Brown et al, 2012; Garibaldi et al, 2005). Homelessness is associated with increased morbidity (Fazel et al, 2014; Hwang, 2001) and early mortality (Barrow et al, 1999; Hibbs et al, 1994; Hwang et al, 2009; Metraux et al, 2011), although the risk that homelessness imparts goes beyond poverty, demographic background, health behaviors, and insurance coverage (Browning & Cagney, 2003; Morrison, 2009), suggesting an important role of the lived environment.…”
Section: Introductionmentioning
confidence: 99%